THE DEVELOPMENT OF INTERACTIVE MEDIA WITH ARTICULATE STORYLINE WITH MOBILE LEARNING BASED ON CIVIC EDUCATION FOR CLASS V STUDENTS - Nidya Chandra MU; Linda Zakiah; Larasati Putri Prasetyo (The University of Kuningan, 2022)
This study aims to develop interactive learning media made with Articulate Storyline with Mobile Learning based on the content of Civics Education in the matter of rights, obligations, and responsibilities in society. This research targets the fifth-grade students of 04 Karet Elementary School. The method used in this RD research is the ADDIE model using the Likert scale evaluation technique. Data analysis was carried out by interviews and questionnaires for teachers and students. In Development, media validation obtained a value of 95% with a very good category. Material validation obtained a value of 91% in the very good category. Language validation obtained a value of 97% with a very good category. The assessment was also carried out by 5 students in the one-to-one trial getting a score of 97% in the very good category, the assessment of 10 students in the small group trial getting a score of 94% in the very good category, and the assessment of 20 students in the trial field test got a score of 97% with very good category. The results of this research on the Development of interactive media products with mobile learning based on the content of Civics Education for Grade V Elementary School can be declared valid and very suitable for online distance learning or use in face-to-face learning activities at school. Furthermore, this learning media can be expanded by using other Civics material.